1969
DOI: 10.1115/1.3571165
|View full text |Cite
|
Sign up to set email alerts
|

The Unsteady Flow and Wake Near an Oscillating Cylinder

Abstract: This paper reports on velocity, pressure, and correlation measurements in the turbulent wake and the adjacent unsteady potential flow of a circular cylinder. Particular attention is given to the effects that attend oscillation of the cylinder in the plane of the lift force. The study was undertaken for four reasons. First was the need to generalize measurement results on the lift force of an oscillating cylinder placed in a flow [1]. Second was the desire to clarify the fluidelastic nature of such forces. Thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
1
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(39 citation statements)
references
References 0 publications
6
30
1
2
Order By: Relevance
“…Since the amplitude of cylinder oscillation is A/D = 0.23 > 0.125, these results are consistent with the observations of Toebes (1969) that sufficiently large amplitude cylinder vibration amplitude should produce a high degree of spanwise correlation. We also find that the tight packing alone does not suppress three-dimensional instabilities.…”
Section: Reynolds Number 200supporting
confidence: 80%
See 1 more Smart Citation
“…Since the amplitude of cylinder oscillation is A/D = 0.23 > 0.125, these results are consistent with the observations of Toebes (1969) that sufficiently large amplitude cylinder vibration amplitude should produce a high degree of spanwise correlation. We also find that the tight packing alone does not suppress three-dimensional instabilities.…”
Section: Reynolds Number 200supporting
confidence: 80%
“…He conjectured that similar effects might be observed in tube bundles. Blevins' investigations confirmed earlier work by Toebes (1969) who showed that a cylinder vibration amplitude of A/D ≥ 0.125 was required to achieve a high degree of spanwise correlation. In the case of tube bundles, it has also been suggested that it is the tight spacing of the bundle that suppresses three-dimensional instability.…”
Section: Introductionsupporting
confidence: 78%
“…Zdravkovich (1982) concluded that the main feature of vortex shedding synchronizing with an oscillating cylinder was to magnify greatly C D and C L , compared with a stationary cylinder. A number of factors contribute to this magnification associated with the lock-in phenomenon, including the reduced vortex formation length (Gerrard 1966;Griffin & Votaw 1972), the prolonged spanwise correlation length (Toebes 1969) and the increased period of vortex shedding (Sarpkaya 1979). The lock-in is in general characterized by (i) the synchronization of the cylinder oscillation with fluctuating lift and vortex shedding from the cylinder (Bishop & Hassan 1964;Govardhan & Williamson 2000), (ii) a short vortex formation region (Griffin 1971;Govardhan & Williamson 2001) (Hover, Tredt & Triantafyllou 1998), (vi) a considerable increase in the vortex strength (Gu, Chyu & Rockwell 1994) or fluctuating velocities (Govardhan & Williamson 2001), (vii) an increase in the oscillation of the separation points (Sarpkaya, 1979), and (viii) a low effective damping ratio, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…all increase with increasing cylinder motion amplitude (e.g. Toebes 1969;Novak & Tanaka 1975) it is reasonable to suggest that the harmonic motion of a long circular cylinder seems to suppress three-dimensionality and produce flows that are more twodimensional than their fixed-cylinder counterparts, at least in the near-wake region. The stochastic nature of turbulent three-dimensional motions is obviously neglected in our model, but we do not believe that this is important in regard to the fundamental mechanisms driving the fluid-structure interaction, because these mechanisms are primarily two-dimensional.…”
Section: Objective and Approachmentioning
confidence: 99%